2022
DOI: 10.7554/elife.81298
|View full text |Cite
|
Sign up to set email alerts
|

Endocytic trafficking determines cellular tolerance of presynaptic opioid signaling

Abstract: Opioid tolerance is well described physiologically but its mechanistic basis remains incompletely understood. An important site of opioid action in vivo is the presynaptic terminal, where opioids inhibit transmitter release. This response characteristically resists desensitization over minutes yet becomes gradually tolerant over hours, and how this is possible remains unknown. Here we delineate a cellular mechanism underlying this longer-term form of opioid tolerance in cultured rat medium spiny neurons. Our r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
1
10
1
Order By: Relevance
“…Instead, chronic morphine treatment did not induce any facilitation in 10 S/T-A mice in this study, suggesting alternative mechanisms are responsible. In studies which have observed presynaptic tolerance, the effect was attributed to a downregulation in the number of functional receptors due to phosphorylation and internalization (Jullié et al, 2022; Jullié et al, 2020). This mechanism is in line with our findings, as tolerance did not develop at MThal-ACC terminals in 10 S/T-A mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, chronic morphine treatment did not induce any facilitation in 10 S/T-A mice in this study, suggesting alternative mechanisms are responsible. In studies which have observed presynaptic tolerance, the effect was attributed to a downregulation in the number of functional receptors due to phosphorylation and internalization (Jullié et al, 2022; Jullié et al, 2020). This mechanism is in line with our findings, as tolerance did not develop at MThal-ACC terminals in 10 S/T-A mice.…”
Section: Discussionmentioning
confidence: 99%
“…Within the presynaptic compartment, multiple adaptations to chronic opioid exposure have been observed; tolerance in some instances (Atwood et al, 2014; Fyfe et al, 2010; Matsui et al, 2014), while enhanced opioid efficacy, or facilitation, in others (Chieng & Williams, 1998; Hack et al, 2003; Ingram et al, 1998; Pennock et al, 2012). MOR phosphorylation also regulates presynaptic cellular tolerance in cultured striatal neurons (Jullié et al, 2022; Jullié et al, 2020), however, the role of phosphorylation in mediating presynaptic facilitation and tolerance in intact brain circuits is not established. Complicating the matter, studies investigating these differences have been done across species and brain regions making it difficult to generalize how a particular cell type or synapse will adapt to repeated opioid exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, extensive future work is needed to directly probe the β-arr–mediated internalization, trafficking, and signaling properties of mGluRs in the synaptic context where little is known about GPCR regulation. Notably, two recent studies of opioid receptors have shown that GRKs and β-arrs can drive rapid endocytosis and long-term down-regulation of receptor function in presynaptic boutons ( 74 , 75 ). However, little is known about lysosomal targeting and potential proteolysis of axonal/presynaptic GPCRs, motivating future work on mGluR8.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic HeLa cells stably expressing N-terminally signal sequence (ss) SEP-tagged DOR were generated by cloning a “CAG promoter, ssSEP-DOR, RGK promoter, PuroR” cassette into a piggyBac transposon plasmid (Addgene #84239), cotransfection of the plasmid with piggyBac transposase, followed by flow cytometry-assisted sorting of GFP-positive cells and puromycin selection. The following published plasmids were used for transient expression: ssfDOR (mouse) ( 7 ), ssfMOR (mouse) ( 7 ), ssfβ2AR (mouse) in pcDNA3.1 ( 5 ), ssfMOR (mouse)-EGFP ( 7 ), ssSEP-(GFP variant Superecliptic pHluorin) DOR (mouse) ( 69 ), β-arrestin2 (bos taurus)-mCherry ( 5 ), GRK2 (bos taurus)-EGFP in pCAGGS-SE ( 70 ), LgBiT-β-arrestin2 (human) in pNBe3 ( 28 ), ManII-BFP2 ( 64 ), and GalT-DsRed2 ( 6 ). N-terminally tagged mRuby2-mGo, mRuby2-mGsi, and mRuby2-mGs ( 33 ) were from Nevin Lambert.…”
Section: Methodsmentioning
confidence: 99%